Interpersonal and Intrapersonal Influences on Sexual Satisfaction in Young Male Couples: Analyses of Actor-Partner Interdependence Models. Issue 2 (12th February 2021) - Newcomb, Michael E.; Swann, Gregory; Ma, Junye; Moskowitz, David; Bettin, Emily; Macapagal, Kathryn; Whitton, Sarah W.
ABSTRACT: Very little research has examined sexual satisfaction in young gay, bisexual, queer, and other men who have sex with men (YMSM). Sexual satisfaction has important implications for individual wellbeing and is a central component of romantic relationship functioning and satisfaction. In order to fill this gap, this study examined interpersonal and intrapersonal factors associated with sexual satisfaction in a large sample of young male couples. Data for these analyses came from the baseline visits of two ongoing randomized controlled trials of 2GETHER, a relationship education and HIV prevention program for young male couples. Participants for the current analytic sample were 419 couples (individual N = 838) from across the United States who were diverse in terms of race/ethnicity, HIV status, and geographic region. Analyses found that relationship functioning (i.e., relationship satisfaction, communication) was positively associated with sexual satisfaction, while not having a specified relationship agreement (i.e., monogamy/non-monogamy agreement) was associated with less sexual satisfaction. Intrapersonal factors (i.e., depression, substance use) were associated with sexual satisfaction, but most of these effects became non-significant in a full multivariate model. Relationship functioning plays a central role in sexual satisfaction and should be addressed in couple-based programs to optimize relationship functioning and sexual health.